Successful perioperative management of cardiac arrest in pregnancy: A case of perimortem caesarean section with favourable maternal and neonatal outcomes - Syama, G M; Rajesh, M C; Lima, P; Vijayan, Winny; Madhusoodanan, Sheila; Gopal, Ajith K; Madathil, Shamnad (Indian Journal of Case Reports, 2025)
Cardiac arrest in pregnancy in an otherwise uncomplicated one is a nightmare for the obstetrician and perioperative physicians. The success of resuscitative attempts depends on how quickly you diagnose the event and react. A multidisciplinary team that is well-trained in resuscitation is the key to success. There should be separate teams to take care of the mother and baby. Support of critical specialists for post-resuscitation care is also crucial. The decision to deliver the baby by caesarean section should be taken without any delay and offer the best chance for the survival of the baby and the mother. Though successful revival of both mother and child is reported in the literature, a 1-year follow-up with both surviving without any neurological deficit is rarely reported in the literature.